Teaching English in Multilingual Classrooms of Higher Education: The Present Scenario - Poudel, Prem Prasad (Journal of NELTA, 2011)
This article aims to discuss some of the major challenges emerged recently in the muItilingual classes in higher education of Nepal. For this, I sampled 20 teachers from four campuses of Kathmandu valley. Similarly, 30 students were selected from those campuses. A set of separate questionnaires was distributed for both teachers and students and at the same time the classes of the teachers were observed. I conducted focus group discussions to elicit the real information from the informants. Major findings show that in the classes of higher education, neither the teachers nor the students are satisfied with the use of medium of instruction. There are communication problems, content delivery problems, comprehension related problems because of language gaps. Finally, in this article, some suggestions are made to make English language teaching in the multilingual settings more effective. Key words: Multilingual classroom; Multiculturalism; Medium of instruction; Multilingual education Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 121-133 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4618